Search for $s$-channel single top-quark production in proton–proton collisions at $\sqrt s=8$ TeV with the ATLAS detector - ATLAS collaboration (2889 authors) (2014)
This Letter presents a search at the LHC for s -channel single top-quark production in proton–proton collisions at a centre-of-mass energy of 8 TeV. The analyzed data set was recorded by the ATLAS detector and corresponds to an integrated luminosity of 20.3 fb −1 . Selected events contain one charged lepton, large missing transverse momentum and exactly two b -tagged jets. A multivariate event classifier based on boosted decision trees is developed to discriminate s -channel single top-quark events from the main background contributions. The signal extraction is based on a binned maximum-likelihood fit of the output classifier distribution. The analysis leads to an upper limit on the s -channel single top-quark production cross-section of 14.6 pb at the 95% confidence level. The fit gives a cross-section of σs=5.0±4.3 pb , consistent with the Standard Model expectation.